Fucosyl glycosides for DC-SIGN targeting: Fucosylation strategies, synthesis and binding studies of model compounds - Chavan, Rohit; Lefèbre, Jonathan; Jochová, Kateřina; Dvořáková, Hana; Rademacher, Christoph; Ménová, Petra (Bioorganic & medicinal chemistry, 2025)
DC-SIGN, a C-type lectin receptor expressed on immune cells, is considered a promising target for immunomodulatory and antiviral therapies. While mannose-based glycomimetics have been extensively studied as DC-SIGN ligands, fucose-based strategies remain underexplored. This study explores the fucosylation of linear alcohols and sugars using eight different fucosyl donors, aiming at designing strategies for the development of fucose-based glycomimetics targeting DC-SIGN. Four types of leaving groups and two different acyl-based protecting groups on the donors were tested. The glycosylation of 3-azidopropan-1-ol exclusively yielded the β-anomer, demonstrating high stereoselectivity. The azido group in the product is versatile, allowing for direct click chemistry reactions or reduction to an amine for further functionalization. Both types of reactions were demonstrated in a model reaction. In the glycosylation of a sugar, a disaccharide moiety of Lewis X antigen was selected as a target molecule. Only one of the eight tested fucosyl donors worked well in this reaction and provided the product in a reasonable yield. The disaccharide was also equipped with the 3-azidopropyl linker, facilitating future modifications. Finally, NMR studies confirmed compatibility of the linker with canonical Ca2+-dependent carbohydrate binding to DC-SIGN, suggesting potential for further development of fucose-based glycomimetics targeting this C-type lectin receptor.
Keywords: Glycosides; Cell Adhesion Molecules; Lewis X; l-fucose; molekulární struktura; Molecular Structure; molekuly buněčné adheze; Glycomimetics; Fucosyl glycosides; DC-SIGN; NMR; receptory buněčného povrchu; lektiny typu C; fukosa; lidé; Lectins, C-Type; Humans; Receptors, Cell Surface; Fucose; glykosylace; Glycosylation; glykosidy